2008
DOI: 10.1248/bpb.31.1469
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Tanshinones and Polyphenolic Extracts of Salvia miltinorrhiza BUNGE after Intravenous Administration in Rats

Abstract: The dry roots of Salvia miltiorrhiza, also called "Danshen" in Chinese, are a well-known traditional Chinese medicinal herb. Because of its better performance and fewer side effects confirmed during the long-time clinical use, Danshen is widely used in traditional Chinese medicinal preparations to treat a number of coronary heart diseases, especially angina pectoris and myocardial infarction. [1][2][3][4] At present, a variety of Danshen products are commercially available, such as Fufang Danshen Tablets and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Therefore, definite pharmacokinetic interactions may be identified. By contrast, Guo et al could not identify which component in tanshinone extracts leads to significant pharmacokinetic alteration of Sal B [22] . Furthermore, the magnitude and the order of the pharmacokinetic sensitivities of various components in Danshen injection could not be obtained from the results.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, definite pharmacokinetic interactions may be identified. By contrast, Guo et al could not identify which component in tanshinone extracts leads to significant pharmacokinetic alteration of Sal B [22] . Furthermore, the magnitude and the order of the pharmacokinetic sensitivities of various components in Danshen injection could not be obtained from the results.…”
Section: Discussionmentioning
confidence: 93%
“…In recent years there have been some reports on the pharmacokinetic interactions of danshen [4,22,23] . For example, Song et al showed the pharmacokinetics of cryptotanshinone and tanshinone IIA to be significantly affected by the oral administration of tanshinone extract in rats [4] .…”
Section: Wwwchinapharcom Chang Bb Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The low urinary excretion of LSB (0.58%) also indicated that renal secretion is not the main excretion pathway [69]. An interesting study was conducted with the aim to evaluate the pharmacokinetic interaction between tanshinones and depsides [70]. Rats were administered i. v. with an emulsion of 10 mg/kg tanshinone extract (equivalent to 4.0 mg/kg TSIIA), 100 mg/kg depside extract solution (equivalent to 61.2 mg/kg SalB), or a mixed extract-loaded emulsion (equivalent to 4.0 mg/kg TSIIA and 61.2 mg/kg SalB).…”
mentioning
confidence: 99%
“…However, no significant differences in the t 1/2 of TSIIA and SalB in the mixed extract-loaded emulsion groups were found compared with that of the corresponding extract groups, except for the high dose groups of TSIIA (p < 0.05). Therefore, a pharmacokinetic interaction occurs between tanshinones and depsides after i. v. administration in rats, which affects the pharmacokinetic process of TSIIA and SalB in vivo [70]. To the best of our knowledge, only one study estimated the pharmacokinetics of depsides in the rat blood and brain by microdialysis sampling [71].…”
mentioning
confidence: 99%